(untitled) (El-Wahat Journal for Research and Studies, 2017)
Strategic planning occupies a prominent position in the administrative process, through it the organization can identify the fact that the internal capabilities as well as its strengths to take advantage of them, and weaknesses to be addressed. It is also the methodology to reduce the degree of uncertainty and risk Associated with variables beyond the control of the organization, As well as to identify the opportunities and threats it faces. And on the grounds that the local administration as an intermediary between the citizen and the central administration, Especially with regard to public service, Nor is the implementation of economic and social policy of the State Like architecture, Work piece, Living, The fight against poverty……etc, However, through which, Good local administration Are adopting plans carefully considered, Thus noon local planning Which means that the measure, which aims to face the future Plans are already prepared to achieve specific goals At the local level, Thus the local Strategic Planning is a balance between the desires and goals of the local community and the natural and human potential. Key words- Strategic planning, local administration, Local Development, Algeria